High Rocks revenge [large type] : a Winters family ranch novel - Mayo, Matthew P. (Winters family ranch novel., 2014)
Returning from selling his fall herd of cattle Niall Winters finds his ranch burned, his uncle dead and his wife missing. With no idea of the horrors that await him he heads out into the season's first snowstorm.